2019
DOI: 10.1097/md.0000000000017824
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of hippocampal volumetry and glucose metabolism for the diagnosis of patients with suspected Alzheimer's disease, using automatic quantitative clinical tools

Abstract: The hippocampus is one of the earliest sites involved in the pathology of Alzheimer's disease (AD). Therefore, we specifically investigated the sensitivity and specificity of hippocampal volume and glucose metabolism in patients being evaluated for AD, using automated quantitative tools (NeuroQuant – magnetic resonance imaging [MRI] and Scenium – positron emission tomography [PET]) and clinical evaluation.This retrospective study included adult patients over the age of 45 years with suspected AD, who had under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 67 publications
(86 reference statements)
0
11
0
Order By: Relevance
“…However, our data suggest that hippocampal atrophy is not part of canine aging, as we could find no clear association between age and hippocampal volumes in either group. Hippocampal atrophy is a key and early feature of human AD, and loss of hippocampal neurons and synapses is strongly associated with cognitive decline in that disorder (Wang et al, 2015;Halliday, 2017;Ferrari et al, 2019). Hippocampal pathology has been documented in brains of dogs with CCD, but hippocampal atrophy has not been demonstrated for this disorder (Schmidt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, our data suggest that hippocampal atrophy is not part of canine aging, as we could find no clear association between age and hippocampal volumes in either group. Hippocampal atrophy is a key and early feature of human AD, and loss of hippocampal neurons and synapses is strongly associated with cognitive decline in that disorder (Wang et al, 2015;Halliday, 2017;Ferrari et al, 2019). Hippocampal pathology has been documented in brains of dogs with CCD, but hippocampal atrophy has not been demonstrated for this disorder (Schmidt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous work in our lab found that tau-PET topography and magnitude are more predictive of longitudinal change in cortical thickness than cross-sectional cortical thickness. 60 It has been postulated that FDG-PET as a biomarker becomes abnormal earlier than MRI in Alzheimer's disease 17,[71][72][73][74] and other neurodegenerative disorders. 68,75 Taken together, these findings suggest that tau pathology may be more closely linked temporally to metabolic than structural abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the functional connectivity features of the regions of interest also predicted the severity of the neuropsychiatric symptoms, as well as the AD pathology (indexed by baseline and change of Aβ/phosphorylated tau ratio) with above 70% accuracy rate. Furthermore, measures of MRI at baseline (GM volumes of specific regions of interest, including the hippocampus) in combination with genetic [apolipoprotein E (APOE) ε4 allele and 19 single nucleotide polymorphisms (SNPs) significantly associated with AD] 35 or hypometabolism (qualitatively investigated with 18F-fluoro-2-deoxyglucose positron emission tomography – FDG-PET) 36 information could predict the progression to AD in MCI cases clinically followed up for 24 months, reaching accuracies higher than 80%.…”
Section: Resultsmentioning
confidence: 99%
“…Using different classification approaches, several studies demonstrated that brain structural MRI (particularly the medial temporal lobe), amyloid and FDG-PET, and genetic features (in particular the APOEε4 allele) better than other imaging and genetic features predicted the distinction between AD and healthy controls and the conversion from MCI to AD. 35 , 36 , 37 , 96 …”
Section: Resultsmentioning
confidence: 99%